Mid-term follow-up results of calcaneal reconstruction for calcaneal malunion - Hong Seop Lee; Woo Jong Kim; Eun Seok Park; Jun Young Kim; Young Hwan Kim; Young Koo Lee (BMC Musculoskeletal Disorders, 2019)
Abstract Background We hypothesized that calcaneal reconstruction can relieve chronic pain due to calcaneal malunion. We report the mid-term follow-up results of calcaneal reconstruction for calcaneal malunion. Methods We reviewed the records of 10 male patients (10 ft) who underwent calcaneal reconstruction for calcaneal malunion between January 2009 and July 2014 at the mid-term follow-up. Talocalcaneal height and angle, calcaneal pitch, calcaneal width, Böhler angle, Stephens classification, and Zwipp classification were evaluated by three orthopedic doctors at each visit (pre-reconstruction, post-reconstruction, and at the last follow-up). Results The mean follow-up period was 67.1 months (range, 48–101 months). The sites of pain before reconstruction were lateral aspect (4 patients), plantar aspect (3 patients), diffuse pain (2 patients), and anterior aspect (1 patient). There was a significant difference in talocalcaneal height, talocalcaneal angle, calcaneal pitch, calcaneal width, and Böhler angle before and after reconstruction (p < 0.05). There was no significant difference between reconstruction and the last follow-up. Radiological measurement agreement was calculated to be moderate to strong (intraclass correlation coefficient: 0.659–0.988). Mean American Orthopedic Foot & Ankle Society Ankle and Hindfoot score improved from 66.50 ± 9.37 pre-reconstruction to 80.30 ± 8.52 at the last follow-up (p < 0.05). The mean visual analog scale score improved from 8.60 ± 1.43 before reconstruction to 3.40 ± 0.84 at the last follow-up (p < 0.05). Most patients were satisfied with the outcome postoperatively. Conclusions Our results showed substantial improvement in the clinical and radiological outcomes after calcaneal reconstruction of calcaneal malunion. This outcome was maintained until the mid-term follow-up. Therefore, calcaneal reconstruction may be a good option for the treatment of chronic pain caused by the malunion of a calcaneal fracture without severe subtalar arthritis. Further prospective studies are needed to test this theory. Level of Evidence: Level IV, Retrospective Case Series.